2013
DOI: 10.1088/0253-6102/60/6/02
|View full text |Cite
|
Sign up to set email alerts
|

Analytic Results in the Position-Dependent Mass Schrödinger Problem

Abstract: We investigate the Schrodinger equation for a particle with a nonuniform solitonic mass density. First, we discuss in extent the (nontrivial) position-dependent mass V (x) = 0 case whose solutions are hypergeometric functions in tanh 2 x. Then, we consider an external hyperbolic-tangent potential. We show that the effective quantum mechanical problem is given by a Heun class equation and find analytically an eigenbasis for the space of solutions. We also compute the eigenstates for a potential of the form V (x… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 70 publications
2
47
0
Order By: Relevance
“…At present days, several discussions can be found in the literature with the purpose of showing different ways of dealing with position dependent-mass systems [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Another context has been discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…At present days, several discussions can be found in the literature with the purpose of showing different ways of dealing with position dependent-mass systems [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Another context has been discussed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…For some relevant mass distributions some phenomenological potentials have been solved in recent years. [21][22][23][24][25][26][27][28] The origin of the PDM approximation can be traced back in the domain of solid state physics. [29][30][31][32][33][34][35][36] For instance, the dynamics of electrons in semiconductor heterostructures has been tackled with an effective mass model related to the envelope-function approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Within the framework of the effective mass approximation, the position dependent mass Schrödinger equation can be given by center[22m(z)]d2ψ(z)dz2ddz[22m(z)]dψ(z)dz+V(z)ψ(z)center=Eψtrue(ztrue) where m ( z ) is the electron PDM and V ( z ) is the QW Gaussian potential which is defined as follows: Vtrue(ztrue)=V0ez2/L2 …”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Also, it has been shown that the developed model can be easily expanded to semiconductor heterostructures . The effect of spatially dependent effective mass in QW structures has become of increasing experimental and theoretical interest . The effects of the position‐dependent effective mass on the optical properties in parabolic QWs have been calculated by Herling and Rustgi, and they have stated that the bound energy levels are lowered with respect to those with constant effective mass .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation